(untitled) (Confluenţe Bibliologice, 2016)
Press Release on section: Library and Information Sciences within the International Scientiﬁc and Practical Symposium REGIONAL COMPETITIVENESS BASED ON THE RESEARCH, INNOVATION AND TECHNOLOGY TRANSFER, Colloquia Professorum “Tradition and Innovation in Scientiﬁc Research”, VI-th edition, dedicated to Professor Nicolae Filip’s Year.